A study of libraries in selected private hospitals in Quezon City - Fajardo, Cynthia Mae Manalaysay, 1946-
In line with the findings of this study, this thesis presents the Minimum Standards for Libraries in Philippine Hospitals with Bed Capacities of 100-125 as its major recommendation. A list of classification schemes for hospital libraries found in the chapter on technical services, and suggestive standard lists for building collections in the chapter devoted to historical background might be helpful to medical and hospital librarians.